Role of endothelin in obstructive jaundice - (:unkn) unknown (My University, 1999)
Mediators responsible for renal changes in obstructive jaundice are not specified. This study is designed to study the role of endothelin-1 (ET-1) in obstructive jaundice in rats. Animals were randomly placed into five experimental groups. Group 1 (N = 3) was the sham-operated group. Group 2 (N = 8) after common bile duct (CBD) ligation, received bosentan, which is a nonselective endothelin receptor blocker, 50 mg/kg/day for seven days. Group 3 (N = 7) received 1 microg/kg/day captopril. Group 4 (N = 7) was given both drugs orally for seven days. Group 5 (N = 6) after CBD ligation, received Arabic gum as the vehicle. Blood was drawn from the infrahepatic vena cava for the determination of ET-1, bilirubin, creatinine, protein oxidation products, hyaluronic acid, and beta-N-acetyl-hexosaminase. Liver tissue samples were obtained to determine glutathione levels. ET-1, protein oxidation products, hyaluronic acid, bilirubin, and creatinine levels increased significantly in the control group when compared with sham. Bosentan effectively prevented ET-1 elevation but could not reverse creatinine or bilirubin elevation. Captopril with or without bosentan was cytoprotective but did not reverse increased creatinine levels. It is concluded that increased ET-1 in obstructive jaundice may be one of the contributing factors of renal damage.
Keywords: Animals; Male; Rats; Random Allocation; Liver; Kidney Diseases; Creatinine; Rats, Sprague-Dawley; Cholestasis; Captopril; Bosentan; Endothelin Receptor Antagonists; Sulfonamides; Hyaluronic Acid; Angiotensin-Converting Enzyme Inhibitors; Bilirubin; Endothelin-1; beta-N-Acetylhexosaminidases